IMPLEMENTATION OF GRAPH COLORING IN UMMUL MUKMININ HIGH SCHOOL STUDENT'S DORMITORY USING WELCH-POWELL ALGORITHM - Putri, Nur Rohmah Oktaviani; Saputra, Edy; Lisnasari, Andi Anita (PATTIMURA UNIVERSITY, 2023)
In Graph Theory, the concept of vertex coloring is an interesting topic because it can be implemented in various fields in everyday life. One of them is the distribution of dorm rooms at a school in Makassar. The placement of dorm rooms is made so that no students from the same class or region are in the same room. The data of region and class will be represented in an adjacency matrix with 137 rows and columns. Furthermore, the coloring will be solved by using the Welch-Powell algorithm. The coloring results obtained were 50 colors. That means, the rooms needed to place 137 students so that no one comes from the same region, and classes are 50 rooms with a maximum capacity of 4 people in each room.